Character Education through Bagan Siapiapi Historical Heritage: A Scientific Approach in the 4.0 Era - Ahmal Ahmal; Asril Asril; Nurdiansyah Nurdiansyah; Jumili Ariyanto (STAI Hubbulwathan Duri, 2025)
In the context of Education 4.0, integrating local cultural heritage into history learning can serve as a powerful medium for character education. This study explores how the historical heritage of Bagan Siapiapi can be utilized in history education to foster students' character values through a scientific approach and digital platforms. This research employed a qualitative descriptive approach, collecting data through document analysis, direct observation, and interviews with local figures. Various historical sources were examined, including books, journal articles, archived documents, and visual media related to historical sites in Bagan Siapiapi. The study identified key historical sites such as the Malay House, Old Shop, Kapitan Oei Hi Tam House, Bagan Madjoe Bank, St. Damian Church, and others. These sites represent historical narratives and contain intrinsic character values, including religious devotion, tolerance, patriotism, and social responsibility. The identified values were analyzed in relation to the historical context and functions of each site. These findings were then mapped to character education goals outlined in national curriculum standards. The historical heritage of Bagan Siapiapi offers a rich and contextual resource for character-based history learning. When implemented through a scientific approach—consisting of observation, questioning, data collection, reasoning, and presentation—this model can enhance students' historical awareness and value-based learning. Future research should explore the measurable impact of this approach on students’ character development and the effectiveness of digital media integration in diverse educational settings.